Household Consumption and Electronic Money Transactions in Indonesia: VECM Approach - Azilla, Widya; Novianda, Besti (Economics Development Analysis Journal, 2024)
The high contribution of household consumption to GDP reflects the significant level of public consumption in Indonesia. This is evident from the annual increase in transactions through digital payment system, which facilitate easier for people to consume goods and services. Previous studies have offered various perspectives on the impact of electronic money transactions on household consumption, in both the short and long run. Therefore, this study aims to analyze the relationship between electronic money transactions and household consumption in Indonesia. By employing the Vector Error Correction Model (VECM) and examining data from 2009Q1 to 2022Q4, the study aims to provide insights into the dynamics of short-term and long-term relationships among electronic money transactions, household consumption expenditure, real income, and interest rates. Based on the results in the short term, it was found that electronic money and real income are positively related to household consumption expenditure in Indonesia. With the increase in electronic money transactions and people's income levels rising, households tend to spend more money, contributing to increased societal consumption. However, this positive relationship does not persist in the long term, suggesting that electronic money does not significantly impact household spending patterns over extended periods. Real income, on the other hand, continues to have a consistent effect in the long term. Furthermore, interest rates do not significantly influence consumption expenditure in either the short or long term. This implies that changes in interest rates do not notably affect consumer behaviour regarding spending habits in Indonesia.